Measurement of the Acid-Binding Capacity of Common Ingredients and Complete Diets Intended for Weanling Pigs - Ethan B. Stas; Mike D. Tokach; Joel M. DeRouchey; Jason C. Woodworth; Robert D. Goodband; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2022)
Some ingredients bind more acid in the stomach than others which can increase gastric pH in weaned pigs, causing decreased protein digestion and allowing pathogenic microorganisms to proliferate. The objective of this experiment was to measure acid-binding capacity at a pH of 4 (ABC-4) of common nursery ingredients and determine additivity in diets. Ingredient categories included: cereal grains, vegetable proteins, animal proteins and milk, vitamin premixes and minerals, amino acids, and fiber sources. A 0.5 g sample of each ingredient was suspended in 50 mL of distilled deionized water and titrated with 0.1 N hydrochloric acid. Sample ABC-4 was calculated as the amount of acid in milliequivalents (meq) required to lower 1 kg of a sample to a pH of 4. Cereal grains were found to have lower ABC-4 compared to other ingredients. Vegetable proteins had higher ABC-4 with more variation than cereal grains. Soy protein concentrate and enzymatically treated soybean meal (ESBM) had higher ABC-4 compared to SBM while fermented soybean meal (FSBM) was lower. Zinc oxide (ZnO) and calcium carbonate (CaCO3) had the highest ABC-4 among all ingredients. Following ingredient analysis, a series of complete diets were analyzed to determine ingredient additivity by comparing the differences between calculated and analyzed ABC-4. Perfect ABC-4 additivity was not found, with all diets having lower analyzed ABC-4 than calculated values; however, the analyzed ABC-4 followed dietary calculated values for higher or lower ABC-4 diet values. These data suggest that ABC-4 diet can be adjusted through selection of ingredients, but feeding trials are needed to determine the impact on pig performance.
Keywords: Acid-binding capacity; ingredients; diets; nursery pig